The Investigation Process of Plantation Crimes in the Production Forest Area - Afwanul Bahri; Ismansyah; Otong Rosadi (Ekasakti Journal of Law and Justice, 2024)
Law No. 18 of 2013 on the Prevention and Eradication of Forest Destruction regulates the unauthorised use of the area. The investigation process of the criminal offence of plantation in a production forest area by investigators at the West Pasaman Police Satreskrim begins with receiving a report. Plantation activities without a business permit in the Production forest area, in Jorong Pigogah Patibubur Nagari Air Bangis, Sungai Beremas District, West Pasaman Regency. After checking the crime scene, it was found that there were palm oil plants aged 1 (one) to 2 (two) years and a wooden hut. Taking the coordinate points shows that the crime scene is included in the production forest area and the reported party cannot show legal legality, so this can be used as preliminary evidence by the investigator. The investigation period was deemed insufficient by investigators to complete the investigation of the case. In addition to running away, the suspects often use the mode of claiming to be indigenous people around the forest. They claim that the land used as a plantation is customary land/customary forest. The obstacles in the investigation process of plantation crimes in production forest areas by investigators at the West Pasaman Police Criminal Investigation Unit are the location of the crime scene which is far from residential areas, the difficulty of reaching the location or crime scene (TKP) to handle criminal cases, the facilities used are still limited as well as the number of members who handle various incidents with the guidance of time all must be fulfilled. The lack of budget makes it difficult to bring in expert witnesses to provide testimony. Experts are needed, especially forest damage experts, legal experts, and planologists. The lack of maximum supporting facilities, such as GPS devices that function to find out the coordinates of the crime scene are only available 2 pieces. This is not proportional to the number of forestry crime cases handled by investigators.